Social backgrounds, oral behaviors and dental service utilization among Thai older adults: data from the national oral health survey - Punkanit Harirugsakul; Issarapong Kaewkamnerdpong; Sudaduang Krisdapong; Piyada Prasertsom; Kornkamol Niyomsilp; Warangkana Vejvithee (College of Public Health Sciences, Chulalongkorn University, 2021)
Purpose - The number of older adults in Thailand is currently increasing. To create the appropriate oral health service for this age group requires an understanding of the factors that are associated with their dental service utilization. This study aimed to determine the associations between social backgrounds, oral behaviors and dental service utilization among Thai older adults. Design/methodology/approach - This was a cross-sectional study on a representative sample of older adults in the 8th Thai National Oral Health Survey (TNOHS). Data of 4,130 Thai older adults were collected through interviews. The association between social backgrounds, oral behaviors and dental service utilization were investigated using chi-square and logistic regression models. Findings - Of the older adults aged 60-74 years old, 38.4% had used dental services in the last 12 months. Smokers used dental services the least (32.1%). Location, income, education and social welfare were significantly associated with dental service utilization. Among the oral behaviors evaluated, smoking was significantly associated with low dental service utilization. Originality/value - Thai older adults with a poor social background including location, income, education, entitlement to the Universal Coverage Scheme (UCS) and smoking made less use of dental services.